Keterkaitan Kualitas Tidur dan Pola Makan terhadap Tingkat Konsentrasi Belajar Mahasiswa Biologi T.Bio1/2022 UINSU - Elvi Zuliani; Soraya Saputri; Rika Rahmawati Situmorang; Syahnur Fadillah Azmi; Mahfuza Delila Harahap; Putri Fazrisina Nst; Annisa Aulia; Resta Gunawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Learning concentration is an important factor in supporting students’ academic success, particularly in Biology study programs that require high levels of accuracy and analytical skills. Learning concentration is influenced by various factors, including sleep quality and dietary patterns. This study aimed to analyze the relationship between sleep quality and dietary patterns and the level of learning concentration among Biology students of class T.BIO1/2022 at Universitas Islam Negeri Sumatera Utara. This study employed an analytic observational approach with a cross sectional design. The research sample consisted of 23 students selected using a total sampling technique. The research instruments included questionnaires on sleep quality, dietary patterns, and learning concentration. Data analysis was conducted descriptively and using cross tabulation. The results showed that students with good sleep quality and regular dietary patterns tended to have higher levels of learning concentration compared to those with poor sleep quality and irregular dietary patterns. Therefore, sleep quality and dietary patterns are important factors that need to be considered to support students’ learning concentration.